Psychophysiological Arousal and Auditory Sensitivity in a Cross-Clinical Sample of Autistic and Non-autistic Anxious Adults - Top Jr., David Nicholas; Luke, Steven G.; Stephenson, Kevin G.; South, Mikle (Frontiers in Psychiatry, 2019)
Many autistic people report overwhelming sensory experiences and also elevated levels of anxiety. Understanding how these experiences are linked to each other can contribute to improved support and intervention for reducing sensory overload and anxiety. This study included 95 young adult participants including autistic adults, non-autistic adults reporting to a psychotherapy clinic with high levels of anxiety, and neurotypical adults with no psychiatric concerns. We measured pupil size using eye tracking hardware and software including a baseline task with no auditory stimulus and two blocks of simple auditory habituation. In a subset of 80 participants we also measured self-report levels of sensory processing, anxious apprehension, and intolerance of uncertainty. The autism group showed atypical sensory processing on all four measured domains. Dimensional analyses across all participants showed significant associations between sensory processing, intolerance of uncertainty, and anxious arousal/worry. While there were no group differences in the rate of auditory habituation, the autism group showed significantly larger pupil size than other groups at baseline, which persisted across the duration of the experiment and could indicate chronic hyperarousal in many autistic people. Treatment for anxiety in autism should be informed by knowledge of unique aspects of anxiety in autism and account for common challenges with sensory experience.